Impact of gut microbiome on skin health: gut-skin axis observed through the lenses of therapeutics and skin diseases - Md. Rayhan Mahmud; Sharmin Akter; Sanjida Khanam Tamanna; Lincon Mazumder; Israt Zahan Esti; Sanchita Banerjee; Sumona Akter; Md. Rakibul Hasan; Mrityunjoy Acharjee; Md. Sajjad Hossain; Anna Maria Pirttilä (Gut Microbes)
The human intestine hosts diverse microbial communities that play a significant role in maintaining gut-skin homeostasis. When the relationship between gut microbiome and the immune system is impaired, subsequent effects can be triggered on the skin, potentially promoting the development of skin diseases. The mechanisms through which the gut microbiome affects skin health are still unclear. Enhancing our understanding on the connection between skin and gut microbiome is needed to find novel ways to treat human skin disorders. In this review, we systematically evaluate current data regarding microbial ecology of healthy skin and gut, diet, pre- and probiotics, and antibiotics, on gut microbiome and their effects on skin health. We discuss potential mechanisms of the gut-skin axis and the link between the gut and skin-associated diseases, such as psoriasis, atopic dermatitis, acne vulgaris, rosacea, alopecia areata, and hidradenitis suppurativa. This review will increase our understanding of the impacts of gut microbiome on skin conditions to aid in finding new medications for skin-associated diseases.